2018
DOI: 10.1002/eji.201847583
|View full text |Cite
|
Sign up to set email alerts
|

Sca‐1+ cardiac fibroblasts promote development of heart failure

Abstract: The causative effect of GM-CSF produced by cardiac fibroblasts to development of heart failure has not been shown. We identified the pathological GM-CSF-producing cardiac fibroblast subset and the specific deletion of IL-17A signaling to these cells attenuated cardiac inflammation and heart failure. We describe here the CD45 CD31 CD29 mEF-SK4 PDGFRα Sca-1 periostin (Sca-1 ) cardiac fibroblast subset as the main GM-CSF producer in both experimental autoimmune myocarditis and myocardial infarction mouse models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 84 publications
3
37
0
Order By: Relevance
“…GM-CSF has been shown to be upregulated either systemically and/or in the diseased tissues of patients with autoimmune conditions (such as rheumatoid arthritis) 2,26 as well as in conditions that show similarities to late-stage COVID-19, including severe acute respiratory syndrome (SARS) 27 , acute respiratory distress syndrome (ARDS) 28 , cytokine release syndrome (CRS) 29 , haemophagocytic lymphohistiocytosis (HLH) 30 , hyperinflammation associated with graft-versus-host disease (GvHD) 31 and other inflammatory diseases of the lung 32 , heart [33][34][35] and nervous system 21,23,36,37 . GM-CSF-producing T H cells have been identified as being involved in the pathogenesis of various immunological disorders (for example, rheumatoid arthritis 26 , multiple sclerosis 21,22 and sepsis 38 ), reminiscent of the pathogenic T H 17 pathway known to drive disease pathology in multiple autoimmune contexts (for example, psoriasis) 39 .…”
Section: Role In Disease the Aberrant Expressionmentioning
confidence: 99%
“…GM-CSF has been shown to be upregulated either systemically and/or in the diseased tissues of patients with autoimmune conditions (such as rheumatoid arthritis) 2,26 as well as in conditions that show similarities to late-stage COVID-19, including severe acute respiratory syndrome (SARS) 27 , acute respiratory distress syndrome (ARDS) 28 , cytokine release syndrome (CRS) 29 , haemophagocytic lymphohistiocytosis (HLH) 30 , hyperinflammation associated with graft-versus-host disease (GvHD) 31 and other inflammatory diseases of the lung 32 , heart [33][34][35] and nervous system 21,23,36,37 . GM-CSF-producing T H cells have been identified as being involved in the pathogenesis of various immunological disorders (for example, rheumatoid arthritis 26 , multiple sclerosis 21,22 and sepsis 38 ), reminiscent of the pathogenic T H 17 pathway known to drive disease pathology in multiple autoimmune contexts (for example, psoriasis) 39 .…”
Section: Role In Disease the Aberrant Expressionmentioning
confidence: 99%
“…For example, periostin-expressing cardiac fibroblasts, genetically modified to lose IL-17RA and therefore IL-17 signaling, reduce their production of the pro-fibrotic growth factor GM-CSF (granulocyte-macrophage colony stimulating factor), effectively limiting cardiac inflammation and tissue death. 161 The secretome of fibroblasts in cardiac fibrosis thus appears to be reciprocally regulated by immune cell secretomes. Similarly, in wounded skin, the cross-talk between macrophage and adipocyte precursors determines the heterogeneous composition myofibroblasts in the wound with impact on skin regeneration and scarring.…”
Section: Regulatory Functions Of Fibroblastsmentioning
confidence: 99%
“… 50 GM-CSF has been reported to be expressed by cardiac fibroblasts in models of Kawasaki disease and myocarditis. 51 , 52 Epithelial cells can produce GM-CSF in response to allergenic stimuli 53 , 54 and such production can restore alveolar barrier function. 55 In addition, studies also reported that endothelial cells can produce GM-CSF in response to pro-inflammatory cytokine stimulation.…”
Section: Gm-csf Biologymentioning
confidence: 99%